(untitled) (TAMADDUN NURI JURNALI, 2024)
The article examines controversial issues about the grammatical status of numbers in the Russian language, highlighting the grounds for their names and volume. The author emphasizes the conceptual aspect of defining parts of speech in scientific discussions about numerals, recommending avoiding extreme points of view.